Ethiopia at the crossroads - Sciacca, Christine, 1976-; Gervers, Michael, 1942- (The Walters Art Museum, 2023)
"Ethiopia at the Crossroads celebrates the artistic traditions of Ethiopia from their origins to the present day, spanning over 1,700 years of history. Seated in the Horn of Africa between Europe and the Middle East, the country is an intersection of diverse climates, religions, and cultures. This landmark catalogue examines Ethiopian art as representative of the nation's notable history and demonstrates the enormous cultural significance of this often-overlooked African nation through the themes of cross-cultural exchange and the human role in the creation and movement of art objects. It features more than 250 images of objects including painted icons, illuminated manuscripts, coins, textiles, metalwork, and carved wooden crosses in addition to works by contemporary Ethiopian artists. Because the artistic production of Ethiopia is still relatively unknown to Western audiences, Ethiopia at the Crossroads provides an accessible overview of the history and culture of the region. The book includes a series of scholarly essays that expand upon the themes and historical moments of encounter between Ethiopia and surrounding cultures, as well as an illustrated checklist of objects in the exhibition and technical findings of the Walters conservation team"--